2018
DOI: 10.1074/jbc.ra118.005134
|View full text |Cite
|
Sign up to set email alerts
|

Endo-fucoidan hydrolases from glycoside hydrolase family 107 (GH107) display structural and mechanistic similarities to α-l-fucosidases from GH29

Abstract: Fucoidans are chemically complex and highly heterogeneous sulfated marine fucans from brown macro algae. Possessing a variety of physicochemical and biological activities, fucoidans are used as gelling and thickening agents in the food industry and have anticoagulant, antiviral, antitumor, antibacterial, and immune activities. Although fucoidan-depolymerizing enzymes have been identified, the molecular basis of their activity on these chemically complex polysaccharides remains largely uninvestigated. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 54 publications
10
70
0
Order By: Relevance
“…FunA was incompetent to hydrolyze sulfated fucans from F. vesiculosus , A. nodosum and M. pyrifera ( Supplementary Table S2 ), which were the effective substrates of GH107 enzymes. Currently, the GH107 family is the only reported fucanase GH family, and its enzymes all exhibited endo-1,4-fucanase activity: MfFcnA was specifically active on α-1,4 glycoside bonds in type II sulfated fucans from F. vesiculosus and A. nodosum (the primary structures were shown in Supplementary Figure S2 ; Schultz-Johansen et al, 2018 ); Fp277 and Fp279 could cleave α-1,4 glycoside bonds in A. nodosum ( Schultz-Johansen et al, 2018 ); P5AFcnA and P19DFcnA showed activity on sulfated fucan from M. pyrifera ( Vickers et al, 2018 ), though the primary structure of M. pyrifera was poorly defined. It has not been reported yet whether the current GH107 enzymes could act on α-1,3 glycosidic linkages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…FunA was incompetent to hydrolyze sulfated fucans from F. vesiculosus , A. nodosum and M. pyrifera ( Supplementary Table S2 ), which were the effective substrates of GH107 enzymes. Currently, the GH107 family is the only reported fucanase GH family, and its enzymes all exhibited endo-1,4-fucanase activity: MfFcnA was specifically active on α-1,4 glycoside bonds in type II sulfated fucans from F. vesiculosus and A. nodosum (the primary structures were shown in Supplementary Figure S2 ; Schultz-Johansen et al, 2018 ); Fp277 and Fp279 could cleave α-1,4 glycoside bonds in A. nodosum ( Schultz-Johansen et al, 2018 ); P5AFcnA and P19DFcnA showed activity on sulfated fucan from M. pyrifera ( Vickers et al, 2018 ), though the primary structure of M. pyrifera was poorly defined. It has not been reported yet whether the current GH107 enzymes could act on α-1,3 glycosidic linkages.…”
Section: Resultsmentioning
confidence: 99%
“…Schultz-Johansen et al, 2018); Fp277 and Fp279 could cleave α-1,4 glycoside bonds in A. nodosum (Schultz-Johansen et al, 2018); P5AFcnA and P19DFcnA showed activity on sulfated fucan from M. pyrifera (Vickers et al, 2018), though the primary structure of M. pyrifera was poorly defined. It has not been reported yet whether the current GH107 enzymes could act on α-1,3 glycosidic linkages.…”
Section: Action Mode Of Funa Revealed By Hpsec-ridmentioning
confidence: 99%
See 1 more Smart Citation
“…105 Recently, fucoidanases from marine Proteobacteria that are able to degrade brown algae have gained increasingly attention due to the beneficial biomedical properties of fucoidan derived oligosaccharides. 106,107 Heterologous expression has been a powerful tool to identify novel gene functions, but it becomes more cumbersome when gene fragments exceed 10 kb. 25 However, most biosynthetic pathways involve dozens of proteins that catalyze and regulate the production of secondary metabolites and thus are often larger than 10 kb and some may even exceed 100 kb.…”
Section: Heterologous Expression Of Bgcs From Marine Proteobacteriamentioning
confidence: 99%
“…KDH14 isolated from abalone intestine is a novel species that possesses a gene cluster encoding putative l -fucose transporter (FucT), l -fucose mutarotase (FucU), l -fucose isomerase (FucI), l -fuculokinase (FucK), and l -fucose operon activator (FucR), indicating its potential involvement in l -fucose metabolism. Abalone feeds on brown seaweeds containing fucoidan and is a good source of fucoidan-degrading enzymes, which can degrade the polymeric fucoidan into its monomeric l -fucose [2527]. In this study, Raoultella sp.…”
Section: Discussionmentioning
confidence: 99%